Kajian Pengaruh Geometri Jalan Terhadap Konsumsi Bahan Bakar Alat Angkut - Dimas Gumelar; Zaenal; Elfida Moralista (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. PT XYZ Tbk is a company engaged in the mining industry with one of its commodities in the form of bauxite located in Sanggau Regency, West Kalimantan Province. In the actual conditions in the research area there are several road geometries that are not in accordance with the standards set so that the production target is not achieved. In this research process, the road geometry at Bukit 30 Site is focused on the standardization of the hauling road to the washing plant area. Analysis using the comparative method is carried out on road geometry that refers to the Decree of the Minister of Energy and Mineral Resources No. 1827 of 2018 and the American Association of State Highways and Transportation Officials Based on the actual research results, the actual productivity in the field of hauling equipment is 32.23 BCM / hour / tool with an average fuel consumption of 10.06 liters / hour and a Fuel Ratio of 0.31 liters / BCM. After simulating the road geometry improvement process using software, recommendations are obtained to increase tool productivity and reduce Fuel Ratio with road grade standardization of no more than 8%. Then obtained an increase in productivity of 69.4 BCM / hour / tool recommendations with the achievement of production of 126,469.04 tons / month with an average fuel consumption of 7.35 liters / hour and a Fuel Ratio of 0.1 liters / BCM. Abstrak. PT XYZ Tbk merupakan perusahaan yang bergerak di bidang usaha industri pertambangan dengan salah satu komoditasnya berupa bauksit yang berlokasi di Kabupaten Sanggau, Provinsi Kalimantan Barat. Pada kondisi aktual di daerah penelitian terdapat beberapa geometri jalan yang tidak sesuai dengan standar yang ditetapkan sehingga, target produksi tidak tercapai. Dalam proses penelitian ini dilakukan terhadap geometri jalan pada Site Bukit 30 yang berfokus pada standarisasi jalan hauling menuju area washing plant. Analisis menggunakan metode komperatif dilakukan terhadap geometri jalan yang mangacu pada Keputusan Menteri ESDM No. 1827 tahun 2018 dan American Association of State Highways and Transportation Officials Berdasarkan hasil penelitian secara aktual maka didapatkan produktivitas aktual di lapangan alat angkut 32,23 BCM/jam/alat dengan rata-rata konsumsi bahan bakar alat angkut 10,06 liter/jam dan Fuel Ratio sebesar 0,31 liter/BCM. Setelah melakukan proses simulasi perbaikan geometri jalan menggunakan perangkat lunak maka didapatkan rekomendasi untuk peningkatan produktivitas alat dan pengurangan Fuel Ratio dengan standarisasi grade jalan tidak lebih dari 8%. Maka didapatkan peningkatan produktivitas rekomendasi alat angkut 69,4 BCM/jam/alat dengan tercapainya produksi sebesar 126.469,04 ton/bulan dengan rata-rata konsumsi bahan bakar alat angkut 7,35 liter/jam dan Fuel Ratio sebesar 0,1 liter/BCM.